(untitled) (Bioresearch Communications, 2023)
This study was conducted to investigate the proximate composition of L. sibiricus, an herbaceous medicinal plant, and explore the potential effects of its bioactive compounds, rutin and quercetin. Samples were collected from Dinajpur and Nilphamari to assess proximate composition. Proximate composition analysis revealed variations of ash, starch, fat, protein, non-reducing sugar (sucrose), invert (total) sugar, and reducing sugar contents of L. sibiricus. These findings indicate that proximate compositions and mineral contents varied depending on the growing place, soil and environmental factors. Furthermore, bioinformatics tools were utilized to investigate the effects of bioactive compounds rutin and quercetin of L. sibiricus in Homo sapiens. In this study, both rutin and quercetin interacted with 10 proteins, separately. Each individual protein interacted with another 10 proteins and found 100 proteins for rutin and 99 proteins for quercetin. However, 199 proteins were used to blast search in NCBI database and blasted results found only 177 proteins. Venn diagram analysis showed only four (4) common proteins interacted with rutin and quercetin. Functional annotation analysis revealed both positive and negative regulations of rutin and quercetin for biological process, molecular functions and cellular component in human health. Interestingly, KEGG pathway, compound and drug analysis exhibited that some potential drugs have already been discovered by rutin and quercetin that are mostly used for vascular protectant, ophthalmic, liver function improving agent and antimicrobial activity. A number of genes or enzymes involved in rutin and quercetin biosynthesis pathway retrieved in KEGG database. This study revealed that genetic engineering might enhances the biosynthesis of rutin and quercetin in honeyweed that could be utilized for production of valuable drug in industry for controlling different human and animal diseases in Bangladesh. Bioresearch Commu. 10(1): 1398-1412, 2024 (January)